2018
DOI: 10.1007/s00167-018-5164-3
|View full text |Cite
|
Sign up to set email alerts
|

A load-measuring device can achieve fine-tuning of mediolateral load at knee arthroplasty but may lead to a more lax knee state

Abstract: Purpose A balanced knee arthroplasty should optimise survivorship and performance. Equilibration of medial and lateral femorotibial load requires guided judicious pericapsular ligament release. The null hypothesis was that there would be no difference between use of a tensiometer device and a remote load sensor final load transfer across the joint through functional arc of motion. Methods A cadaveric study, using eight knees, was performed to define the impact of an est… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 35 publications
1
23
0
Order By: Relevance
“…The results are in agreement to the ones found by other recent experimental (Manning, Blain, Longstaff, & Deehan, 2018) and shown that the tension necessary to stabilize a knee joint in different ligament conditions is way lower than the ones usually applied via tensioners nowadays.…”
Section: Resultssupporting
confidence: 92%
“…The results are in agreement to the ones found by other recent experimental (Manning, Blain, Longstaff, & Deehan, 2018) and shown that the tension necessary to stabilize a knee joint in different ligament conditions is way lower than the ones usually applied via tensioners nowadays.…”
Section: Resultssupporting
confidence: 92%
“…In a cadaveric study with 7 knees, 26) the tensiometer failed to achieve gap balance for 3 of 7 TKAs; the sensor was able to guide final soft-tissue balancing to equilibrate compartmental loads through the full range of motion. The rectangular flexion and extension gaps may be achieved by modern distraction tensiometers; however, they only measure soft-tissue behavior at 2 points of motion and are very easily influenced by rotational malposition of the femoral and tibial components.…”
Section: Advantagesmentioning
confidence: 98%
“…The rectangular flexion and extension gaps may be achieved by modern distraction tensiometers; however, they only measure soft-tissue behavior at 2 points of motion and are very easily influenced by rotational malposition of the femoral and tibial components. 26 27) In addition, gap equivalence during distraction does not necessarily equate to a balanced load, 9) unless there are equivalent Young's moduli for the medial and lateral soft tissues. 26 28) Sensors can overcome the limitations of the distraction tensiometer in terms of femorotibial incongruence and Young's moduli.…”
Section: Advantagesmentioning
confidence: 99%
“…Ligament balancing in TKA is an important step that effects postoperative function and longevity of prosthesis. 3 Medial release of fixed contracture of medial soft tissue in varus OA knee is necessary to obtain perfect gap balancing. 5 MNP is one technique that has reported to be successful in reaching this goal.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 Coronal ligament balancing is one of the most important steps that effects outcome and the longevity of implants. 3 In varus osteoarthritis (OA) knee, medial soft tissue is contracted while the lateral soft tissue is elongated. 4 Therefore, medial soft tissue release is performed to correct knee alignment.…”
Section: Introductionmentioning
confidence: 99%